The Determinants of Malaysian Consumers’ Green Products Purchase Decision - Jayanty KUPPUSAMY; Ajitha ANGUSAMY; Kavitha BALAKRISHNAN; Yi Hern TAN (Communications of International Proceedings, 2020)
Concern for the environment has been growing over the years. One area of concern is the awareness towards green product. A number of studies have been done on the green product purchase decision. However, limited studies have been done from the Malaysian perspective.  Therefore, the current study’s purpose is to examine which factors influence consumers’ green product purchase decision of Malaysian consumers. The respondents are Malaysian adults and data was collected from 181 respondents. The factors studied include social influence, green product experience, supporting environmental protection, drive for environmental responsibility and attitudes toward green purchasing. The result indicates all except for supporting environmental protection, influences the green products’ purchase decision. Therefore, marketers of green product should focus on these factors in order to encourage increase in purchase of green products.
Keywords: Purchase Decision; Social Influence; Green Product Experience; Environmental Protection.